On the Refutability of Untranslatability: A Cross-cultural Approach - Rahimy, Ramin (Iranian Journal of Translation Studies, 2004)
This paper aims at introducing ‘untranslatability’ and examining its dimensions. Focusing on the issue is noticeable and significant in that any comment on its various aspects may lead us to provide a solution for the attainment of a closer TL equivalent for different units of translation which lack an exact equivalent, or which seems very difficult to find an equivalent for. Here, untranslatability is defined from different scholars’ points of view, then, its refutability conditions are discussed with a focus on some reasons.